The influence of the use of absorbent muds and permeable surfaces to reduce surface runoff - Suchanek-Gabzdyl, Ewa (Instal, 2023)
Rainwater is the main component of water resources, which ensures the replenishment of surface and underground waters. Due to the unsustainable development of urban and rural areas, precipitation is beginning to be perceived as a source of threat. This situation leads to the emergence of a new phenomenon known as urban flooding. Urban areas that had no issues with rainwater drainage several decades ago now transform into floodplains after heavy rainfall. The second important aspect is climate change. The occurrence of numerous weather anomalies, such as torrential rain, in recent years has resulted in the formation of flash floods in cities, causing sudden inundation of lower-lying areas, often creating a surge wave. To address these problems, rainwater retention and infiltration devices are increasingly being employed in cities. Such measures do not require the reconstruction of existing storm drains and can be implemented through the creation of rain gardens, absorbent mounds, or permeable surfaces, for example. Furthermore, these initiatives enhance groundwater resources and enrich the landscape and aesthetics of cities, leading to an improved microclimate and better living conditions for the urban population.
Keywords: rainwater; surface runoff; absorbent troughs; permeable surfaces